(untitled) (Research, Society and Development, 2023)
The present work analyzed difficulties and challenges of hybrid teaching, the conceptions about the pedagogical practice of teachers of a full-time school in the city of Manaus-AM. This research aims to identify what were the difficulties facing the pedagogical practices in this period of non-face-to-face classes. The pedagogical practice was investigated from the planning and systematization of the dynamics of the learning processes to the contents and activities that were developed during this period. A qualitative methodology was adopted, using individual interviews through a questionnaire as an instrument. The results obtained demonstrate the importance of knowing how these practices and tools used by teachers can impact and interfere in the educational process.